If there is a stable relationship between climate change and civil war in Sub-Saharan Africa? A replication study of Miguel et al. (The Journal of Political Economy, 2004) - Sherin Khalifa; Christian H. C. A. Henning (Kiel University, Department of Agricultural Economics, Chair of Agricultural Policy, 2020)
We replicated the findings of Miguel and his co-authors, who find a significant negative relationship between economic shocks and the likelihood of civil conflict in Sub-Saharan Africa (SSA) for the period 1981- 1999, using rainfall growth as an instrumental variable for the economic growth rate. The replication of this study is successfully performed. Furthermore, we apply a robustness test to the results using new cross-country panel data, with different measurements, and econometric specifications. The results appear to be sensitive to changes in data sources that use different methods of making the data available, although we find partly the same patterns between weather and economic growth rate, and between the income growth and the likelihood of civil conflict, like Miguel et al. (2004) for SSA period 1981-1999.
urn:nbn:de:gbv:8:3-2021-00235-0
Keywords: 330; Rainfall; economic growth rate; conflict; Sub-Saharan Africa